Bref aperçu d’un modèle à forme réduite de prévision de la dépense nationale brute au Canada - Duguay, Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
This paper presents a critical evaluation of a St-Louis type monetarist reduced-form model for Canada. The model centres on two equations estimated over the 1957-1977 sample period. An expenditure equation relates the growth of nominal GNE to the rate of monetary expansion and to changes in autonomous expenditure. The split between real growth and inflation is modelled through a simple Phillips curve with adaptive expectations.The dynamic properties of the model are discussed, and illustrated with simulations of alternative monetary growth paths. The analysis reveals some disturbing characteristics of this type of model. For instance, the responses of GNE to money supply changes or to price shocks are not symmetrical though both represent the same shock to real money supply. The price response to a monetary shock, while more plausible than in most large macroeconomic models, remains inadequate since increased monetary expansion results in higher real money supply accompanying higher inflation. The author nevertheless leaves the impression that reduced form models are a useful starting point for econometric research; their limitations are only an invitation to further refinements.